The Voyage of H.M.S. Cove , Captain James Clark Ross, 1835–36 - Jones, A. G. E. (Polar Record, 1950)
On 4 December 1885, thirty-four Hull shipowners sent to the Admiralty a Memorial stating that, on 11 October, eleven whaling ships had been left by the Alfred, Hull, closely beset in Davis Strait between lats. 69° N. and 70° N., and longs. 60° W. and 65° W., frozen in by the early approach of winter. It was stated that there was little prospect of their speedy liberation. The crews numbered upwards of 600 souls. The value of the vessels was estimated at no less than £59,000 excluding the value of oil and whalebone worth £13,500. The ships were as follows: